2019
DOI: 10.22271/ortho.2019.v5.i4q.1805
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome of distal tibia fracture treated with locking compression plate using minimally invasive percutaneous plate osteosynthesis technique (MIPPO): A prospective study

Abstract: Introduction: Treating distal tibia fracture is a greater challenge for surgeons to manage even today. The difficulty is due to its poor blood supply and limited soft tissue envelope. Various techniques are now available for the treatment of tibia fractures. The occurrence of implant failure, skin necrosis, infection and malunion are high in case of distal tibia fractures. Aims/Objective: Our aimed was to analyze the functional outcome of distal tibia fractures treated by MIPPO Technique using the American Ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 9 publications
0
0
0
Order By: Relevance
“…In this study, the mean AOFAS total score at three months was found to be 74.46 + 8.278, which was almost similar to a study by Illur et al [8] (Table 7). The mean duration for radiological union in this study was 22 weeks, which is similar to other studies (Table 9).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, the mean AOFAS total score at three months was found to be 74.46 + 8.278, which was almost similar to a study by Illur et al [8] (Table 7). The mean duration for radiological union in this study was 22 weeks, which is similar to other studies (Table 9).…”
Section: Discussionsupporting
confidence: 90%
“…In this scale, both subjective and objective variables were used and they were classified into three main categories, which consisted of pain (40 points), function (50 points), and alignment (10 points). Based on the total AOFAS score at each follow-up visit, four outcomes (excellent, good, acceptable, and bad) were derived (Table 1) [8].…”
Section: Postoperative Managementmentioning
confidence: 99%